2018
DOI: 10.1016/j.jaut.2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of neuropsychiatric lupus: The relative roles of the blood-cerebrospinal fluid barrier versus blood-brain barrier

Abstract: The pathogenesis of neuropsychiatric lupus (NPSLE) is believed to include the entry of circulating neuropathic antibodies to the brain via a pathologically permeable blood-brain barrier (BBB). Nevertheless, direct evidence of BBB pathology or mechanisms underlying BBB dysfunction is missing. Here, we examined BBB integrity in an established NPSLE mouse model (MRL/fas). Surprisingly, challenging the barrier with various exogenous tracers demonstrated insignificant changes in BBB permeability. Furthermore, elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 54 publications
1
48
1
1
Order By: Relevance
“…Further evaluation of the CP was performed by electron microscopy because this modality allows for direct evaluation of intercellular interactions as well as subcellular features of the tissue, including cell localization. TEM revealed that lymphocytes were often found engulfed by CP epithelial cells and localized within their membrane borders ( Figure 8A), with no apparent disruption of interepithelial tight junctions ( Figure 9B), which together are strongly suggestive of transepithelial T cell migration, a finding that we recently described more extensively elsewhere (37). SEM demonstrated a normal-appearing CP in MRL/+ mice ( Figure 8B), whereas there was extensive leukocyte infiltration and stromal expansion in the MRL/lpr mice ( Figure 8C).…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…Further evaluation of the CP was performed by electron microscopy because this modality allows for direct evaluation of intercellular interactions as well as subcellular features of the tissue, including cell localization. TEM revealed that lymphocytes were often found engulfed by CP epithelial cells and localized within their membrane borders ( Figure 8A), with no apparent disruption of interepithelial tight junctions ( Figure 9B), which together are strongly suggestive of transepithelial T cell migration, a finding that we recently described more extensively elsewhere (37). SEM demonstrated a normal-appearing CP in MRL/+ mice ( Figure 8B), whereas there was extensive leukocyte infiltration and stromal expansion in the MRL/lpr mice ( Figure 8C).…”
Section: Resultssupporting
confidence: 65%
“…Additionally, the CP has been implicated in human NPSLE, as evidenced by MRI (18,49) as well as anecdotal reports identifying IgG deposition within the CP basement membrane in biopsy samples (16). Furthermore, our recent work evaluating BBB function and routes of immune penetration into the CNS has proved revealing in the model used herein; BBB function in particular as it relates to interendothelial tight junctions appears to be mostly conserved, and the CP is in fact a conduit for immunoglobulin transmission and lymphocyte migration (37). The various potential modes of immune migration through the CNS in SLE have been recently reviewed, including discussion of the relative roles of the BBB and CP, as well as the potential involvement of dural lymphatics and the glymphatic pathways (46).…”
Section: Discussionmentioning
confidence: 65%
“…However, no new potential agents are on the horizon for NPSLE. Understanding the pathophysiologic mechanisms leading to NPSLE is essential for the evaluation and design of effective interventions (30). Several difficult clinical situations need to be further elucidated.…”
Section: Future Directionsmentioning
confidence: 99%
“…Historically, studies in mice have suggested that there need to be a "second hit," namely a breach in the BBB for antibodies to access the brain, however, was recently challenged by studies failing to find an effect of BBB disruption [26], but rather an impact of BCSFB disruption [27]. As such, using exogenous tracers, Gelb et al failed to find significant changes in BBB permeability in MRL/lpr mice but found abnormal function of the BCSFB in the choroid plexus, a potential site for lymphocyte infiltration [27]. Further studies are needed to identify the relative significance of BBB and/or BCSFB disruption in different animal models and in response to different inflammatory factors including cytokines and autoantibodies.…”
Section: Three Types Of Barriersmentioning
confidence: 99%